A Wireless LAN Protocol for Initial Access Authentication (International Journal of Engineering and Computer Science, 2014)
Nowadays there is widespread use of WLAN enabled devices, so it is equally important to have efficient initial link setup mechanism. In this paper a fast access authentication process is implemented which is faster than current 802.11i. Through experiments, it is observed that the inefficiency of 802.11i is due to its design from the framework perspective which introduces too many messages. Due to more number of round-trip messages in 802.11i authentication delay is intolerable under some scenarios. To overcome this, an efficient initial access authentication protocol FLAP is proposed which introduces two round-trip messages with authentications and key distribution. Proposed FLAP protocol scheme is more secure than 4-way handshake protocol. Simulations are conducted using different scenarios like Authentication delay, Throughput, Packet Delivery Ratio (PDR), Packet Drops are measured for different scenarios and compared between the 802.11i and FLAP protocol. The results show that the FLAP is more advantageous when WLAN gets crowded.